The Role of Contemporary Pedagogical Technology in ECE: A Systematic Literature Review - Novi Anggraeni; Aan Listiana (Universitas Pendidikan Ganesha, 2023)
Early Childhood Education (PAUD) is a critical stage in a child's development that lays the foundation for lifelong learning and success. The use of technology in PAUD is effective for improving learning and development outcomes. Contemporary pedagogical technologies such as interactive media, mobile applications, and educational software have been identified as potential tools for improving the quality of ECD. This literature review aims to analyze efficacy of educational technology in boosting the learning and development of young children. In this literature review, the writers selected relevant and accurate studies from restricted academic sources such as Scopus and Crossref to gather research data, which were then categorized according to PRISMA criteria. The first search yielded 134 articles, which were then whittled down to 20 papers acceptable for closer examination. This study results reveal a lack of instructor competency in the use of technology among ECE classroom instructors, preventing educators from focusing on the use of technology in early childhood education. This is due to the fact that early childhood educators are less equipped for the theory and practice of modern educational technologies, such as learning software, mobile apps, and interactive media, which may increase the cognitive, linguistic, and social capacities of young children. In the meanwhile, educational technology may assist in bridging the learning gap between children with special needs and those without access to formal schooling.